2017
DOI: 10.1037/str0000022
|View full text |Cite
|
Sign up to set email alerts
|

Working with the stress of errors: Error management strategies as coping.

Abstract: Workplace error management research has focused on performance, especially in training settings. The connection of error management strategies to employees’ well-being has not been examined despite the fact that errors can include making mistakes that are threatening to one’s sense of self-worth. The present study connects the number of errors committed to employees’ psychological strain through interpretations of errors, or error management. The transactional theory of stress provides a framework for the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…However, error management theory is only concerned with leveraging errors for improved future performance, and only recently (King and Beehr, 2017), researchers have begun focusing on the complex impact that making a mistake can have on the employee's well-being. King and Beehr (2017) used the transactional theory of stress (Lazarus and Folkman, 1984) to explain how errors may lead employees to experience emotional strain, depending on how those errors are appraised. This theory consists of two stages of appraisal: primary appraisal is focused on the degree of harm or threat in the situation, and secondary appraisal is focused on the person's perceived ability to cope with the situation that has been deemed threatening or harmful in the first stage.…”
Section: Acute/episodic Underperformance As a Stressormentioning
confidence: 99%
See 1 more Smart Citation
“…However, error management theory is only concerned with leveraging errors for improved future performance, and only recently (King and Beehr, 2017), researchers have begun focusing on the complex impact that making a mistake can have on the employee's well-being. King and Beehr (2017) used the transactional theory of stress (Lazarus and Folkman, 1984) to explain how errors may lead employees to experience emotional strain, depending on how those errors are appraised. This theory consists of two stages of appraisal: primary appraisal is focused on the degree of harm or threat in the situation, and secondary appraisal is focused on the person's perceived ability to cope with the situation that has been deemed threatening or harmful in the first stage.…”
Section: Acute/episodic Underperformance As a Stressormentioning
confidence: 99%
“…Furthermore, there is likely an interaction between the two underperformance types (see Figure 2C). It is thought that employees who are generally high performers are more likely than underperformers to be able to leverage an error as a learning opportunity and not experience subsequent error strain (King and Beehr, 2017). Therefore, the consequences or outcomes for acute/episodic underperformance are likely more severe when the employee is chronically an underperformer.…”
Section: The Interplay Between Chronic and Acute/ Episodic Underperfomentioning
confidence: 99%
“…Salient to the development of mental health symptoms in athletes is the concept of psychological strain, characterised by a combination of perceived stress and difficulty coping. Psychological strain can be characterised on a continuum of emotional exhaustion and reaction to stressful experiences (Boswell, Olson-Buchanan, & LePine, 2004), and is likely to occur in situations where an individual believes they do not have sufficient resources to cope (King & Beehr, 2017). Where coping resources are extended beyond an athlete's capacity, stress-related symptoms of psychological strain may emerge (Raedeke & Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are many theories on physical processes and external types of stressors. These may be categorized in two ways: "systemic" stress these are based on psychobiology, and physiology [11] and mental stress developed within the field of cognitive psychology [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Theories On Stressmentioning
confidence: 99%
“…Workplace error management has also been a focus of various studies. Applying the transactional theory of stress frame work King and Beehr has examined the connection of error management strategies to employees' well-being and showed that positive error management (PEM) did not appear to reduce strains, but negative error management (NEM) increased them and difference in the approach between the individual and organization can affect employees' interpretations and management of errors [5]. ICT-based communication is known to be a source of stress.…”
Section: Introductionmentioning
confidence: 99%